Pengaruh Harga Dan Fitur Produk Terhadap Keputusan Pembelian Telepon Pintar - Ermalina Ermalina (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2020)
The purpose of this research is to understand the price and product feature towards purchase decision smartphone V. This research is a quantitative research by using the SPSS Statistic 25 with population unknown and 120 respondents of sample which use smartphone V in South Jakarta who have bought smartphone V. The sample design in this study uses non probability sampling method and purposive sampling techniques. The result of this research data technical used multiple linear regression analysis and it shows significant effect both partially and simultaneously between price and product feature toward purchase decision.